2007
DOI: 10.4049/jimmunol.179.3.1864
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Toluene Diisocyanate Vapor Induces Allergic Rhinitis in Mice

Abstract: Diisocyanates are the leading cause of occupational asthma, and epidemiological evidence suggests that occupational rhinitis is a comorbid and preceding condition in patients who develop asthma. The goal of the present studies was to develop and characterize a murine model of toluene diisocyanate (TDI)-induced rhinitis. Female C57BL/6 mice were exposed to workplace-relevant concentrations of TDI vapor via inhalation for 4 h/day for 12 days with or without a 2-wk rest period and TDI challenge. Mice exposed 12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…We observed similar eosinophil infiltration after TDI-provocation in TDI-sensitized rats (unpublished observation), so it is expected that eosinophil infiltration should be suppressed in the Kujinpretreated group, although we have no data to support this expectation. In TDI-sensitized mice, it has been reported that TDI treatment increases not only Th2-cytokines including IL-4, IL-5, and IL-13 but also Th1 cytokines such as IFN-γ, so the inflammation induced by TDI is associated with a mixed Th1/Th2 immune response (69). In our model rats, the mRNA levels of both Th2-cytokines such as IL-4, IL-5, and IL-13 ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…We observed similar eosinophil infiltration after TDI-provocation in TDI-sensitized rats (unpublished observation), so it is expected that eosinophil infiltration should be suppressed in the Kujinpretreated group, although we have no data to support this expectation. In TDI-sensitized mice, it has been reported that TDI treatment increases not only Th2-cytokines including IL-4, IL-5, and IL-13 but also Th1 cytokines such as IFN-γ, so the inflammation induced by TDI is associated with a mixed Th1/Th2 immune response (69). In our model rats, the mRNA levels of both Th2-cytokines such as IL-4, IL-5, and IL-13 ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Johnson et al developed and characterized a murine model of TDI-induced rhinitis (55). They showed that inflammation induced by TDI is associated with a Th1/Th2 mixed immune response and showed that the lower airways showed no evidence of inflammation and that the inflammation and gene expression changes were isolated to the upper airways.…”
Section: Discussionmentioning
confidence: 99%
“…The IgE release from B cells occurs in the presence of interleukine-4 (IL-4) which can be released from T helper cell type 2 (Th2 cells). TDI is well known to stimulate Th2 cells to elevate IL-4 levels (Ban et al, 2006;Johnson et al, 2007;Sun et al, 2007). Not only chronic asthma but also acute reactions induced by TDI…”
Section: Introductionmentioning
confidence: 99%